Disseminating information about healthcare effectiveness: a survey of consumer health information services. Issue 3 (September 1998) - Entwistle, V A; Watt, I S
Abstract : BACKGROUND: In 1997 a research based information leaflet designed for men considering being screened for prostate cancer was distributed to general practitioners (GPs) and consumer health information services. OBJECTIVES: To investigate consumer health information service staff opinions of the leaflet and the use they made of it. To find out whether such staff would find similar leaflets on other topics useful. DESIGN: A postal questionnaire survey sent to United Kingdom consumer health information services. RESULTS: Consumer health information service staff were enthusiastic about the content and presentation of the leaflet and gave it to many enquirers, including some who had not been given information by their GPs. Respondents were keen to be supplied with similar leaflets about different topics. Some respondents were reluctant to give the leaflet to people enquiring about screening for prostate cancer, for example, because they thought that the leaflet would cause anxiety, or because prostate cancer screening was not freely available locally. CONCLUSION: Consumer health information services can complement information provided by health professionals and make good use of research based information for consumers. However, they may withhold information from some people who might benefit from it and are not well placed to advise people about healthcare options. Strategic thinking is needed to encourage a more integrated approach to giving information and support for patients in making decisions.